The Effect of Liquidity, Profitability And Company Size on Company Valuewith Capital Structure As An Intervening Variable In Manufacturing Companies Listed on The Idx In 2016- 2020 - Panjaitan, Florencia Rani; Minan, H.Kresna; Arief, Muhammad (International Journal of Economics and Management, 2023)
This study aims to determine the effect of liquidity, profitability and company size on firm value with capital structure as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The type of research used in this research is associative. The population in this study were 195 companies, the sampling method used was a purposive sample, with a total sample of 60 companies. The data analysis technique used is path analysis with statistical data processing using the SPSS data processing application version 20.0. The results of this study indicate that liquidity and profitability have an effect on capital structure, while firm size has no effect on capital structure. Liquidity, profitability and capital structure have a significant effect on firm value, while company size has no effect on firm value. Capital structure is able to mediate the effect of liquidity, profitability on firm value, while capital structure cannot mediate the effect of company size on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX).